Efektivitas Ekstrak Akar Kaik-Kaik (Uncaria cordata) Sebagai Feed Additive Terhadap Efisiensi Pemanfaatan Pakan dan Pertumbuhan Ikan Nila (Oreochromis niloticus) - Rozik, Mohamad; Maryani, Maryani; Najamuddin, Anang (Universitas Batangahari Jambi, 2026)
High feed costs (accounting for 60–70% of production costs) and the risks of stress in intensive aquaculture necessitate the use of safe, natural feed additives. Kaik-kaik root (Uncaria cordata) contains bioactive compounds such as alkaloids and flavonoids, which have the potential to enhance fish health and metabolic efficiency. This study aimed to analyze the effectiveness of adding Uncaria cordata root extract as a feed additive on feed utilization efficiency, growth performance, and survival rate of Oreochromis niloticus. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments and three replications, namely P0 (0% as control), P1 (2%), P2 (4%), and P3 (6%) inclusion levels of the extract in the feed. The observed parameters included growth performance (weight gain and specific growth rate/SGR), feed utilization efficiency (feed conversion ratio/FCR and feed efficiency), and survival rate (SR). The results showed that the addition of the extract had a significant effect (P